2010
DOI: 10.2202/1540-8884.1327
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Partisan Gerrymandering: Looking Ahead to the 2010 Congressional Redistricting Cycle

Abstract: This article looks ahead to the 2010 congressional redistricting cycle, and makes the case that the concern over the pernicious effects of partisan redistricting has been significantly over-exaggerated. Those attempting to use partisan control of the apparatus of state government to influence future elections operate under a number of significant constraints, from legal and political factors that inhibit the redistricting process and frequently result in compromise or litigation, to geographical and structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…And indeed, essential to the idea of the “dummymander” is that misestimating future political trends causes not just increased competition but, ultimately, the loss of seats for the gerrymandering party, potentially also leading to loss of partisan control of Congress. Grofman and Brunell’s (2005) original example of the “dummymander” concerned Democratic seats losses under southern Democratic gerrymanders in the 1994 Republican wave election, while Seabrook (2010) showed how Republicans lost a disproportionate number of seats in states they gerrymandered in the consecutive Democratic waves in 2006 and 2008.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And indeed, essential to the idea of the “dummymander” is that misestimating future political trends causes not just increased competition but, ultimately, the loss of seats for the gerrymandering party, potentially also leading to loss of partisan control of Congress. Grofman and Brunell’s (2005) original example of the “dummymander” concerned Democratic seats losses under southern Democratic gerrymanders in the 1994 Republican wave election, while Seabrook (2010) showed how Republicans lost a disproportionate number of seats in states they gerrymandered in the consecutive Democratic waves in 2006 and 2008.…”
Section: Resultsmentioning
confidence: 99%
“…Grofman and Brunell (2005), in a series of short case studies referred to as “dummymanders,” show that many maps drawn by southern Democrats in the 1990s failed to anticipate trends favoring the Republican party. Conversely, Seabrook (2010) argues that the effects of Republican partisan maps were largely washed out by mid-decade partisan trends in the 2000s. However, the global effect of “dummymanders” on competition, and the frequency of their occurrence, is largely still unexamined beyond anecdotal evidence and narrow case studies.…”
Section: Previous Research On Districting and Competitionmentioning
confidence: 99%
“…Almost everything that is known about the national consequences of gerrymandering comes from research conducted on the redistricting cycles that have occurred since the court-led reapportionment revolution of the 1960s. This research typically shows that each of the subsequent rounds of redistricting produced, at best, only a minimal impact on the partisan balance of power in Congress (e.g., Glazer, Grofman, and Robbins 1987;Seabrook 2010;Swain, Borrelli, and Reed 1998).…”
Section: Resultsmentioning
confidence: 99%
“…The image of politicians manipulating district lines for partisan gain suggests that the path to national power may run through the state legislatures. Yet, political-science research on congressional redistricting in the 1970s, 1980s, 1990s, and 2000s has found, at most, only minimal national partisan consequences (e.g., Campagna and Grofman 1990;Seabrook 2010;Swain, Borrelli, and Reed 1998). Taking a historical step back and examining the partisan consequences of redistricting in the late 19th century sheds new light on this debate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation